Proceedings of the 2016 International Conference on Quantitative InfraRed Thermography 2016
DOI: 10.21611/qirt.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography applied for experimental investigation of thermomechanical couplings in Gum Metal

Abstract: Results of initial investigation of thermomechanical couplings in innovative β-Ti alloy called Gum Metal subjected to tension are presented. The experimental set-up, consisting of testing machine and infrared camera, enabled to obtain stress-strain curves with high accuracy and correlate them to estimated temperature changes of the specimen during the deformation process. Both ultra-low elastic modulus and high strength of Gum Metal were confirmed. The infrared measurements determined average and maximal tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Increase in the specimen temperature after it drops due to thermoelastic effect, started from point A ( Figure 1b) revealed dissipative character of the process. This takes place in the range of reversible deformation [1,2] and is caused by a stress-induced phase transformation of martensite-like orthorhombic α″ nanodomains [3,4]. From the points B and C the slope of ΔT vs. ε dependence increases significantly.…”
Section: Resultsmentioning
confidence: 98%
“…Increase in the specimen temperature after it drops due to thermoelastic effect, started from point A ( Figure 1b) revealed dissipative character of the process. This takes place in the range of reversible deformation [1,2] and is caused by a stress-induced phase transformation of martensite-like orthorhombic α″ nanodomains [3,4]. From the points B and C the slope of ΔT vs. ε dependence increases significantly.…”
Section: Resultsmentioning
confidence: 98%
“…are in line with the scheme shown in Figure 4 a and allowed us to indicate the material yield limit with a high accuracy [ 20 , 21 , 22 , 23 ]. In the case of Gum Metal, even the initial experiments conducted by the authors [ 24 , 34 ] showed that the maximal drop in temperature occurred significantly earlier (stage I) than the limit of its recoverable deformation (stages I and I ’ ) as demonstrated in Figure 4 b.…”
Section: Resultsmentioning
confidence: 98%
“…The temperature changes accompanying the material’s deformation enable investigators to determine its yield point [ 19 , 20 , 21 ], analyze the nucleation and development of the strain localization [ 22 , 23 , 24 ], and estimate the energy storage [ 25 ]. Thus, the thorough determination of the effects of thermomechanical couplings can contribute to the knowledge about the behavior of new materials [ 20 , 23 , 26 , 30 , 31 , 32 , 33 , 34 ]. This section concerns analysis of the effects of thermomechanical couplings monitored in the initial stage of Gum Metal loading.…”
Section: Resultsmentioning
confidence: 99%
“…Nessa etapa, a termografia por infravermelho revelou claramente um aumento mais acentuado na temperatura para todas as taxas de deformação. Segundo GOLASINSKI et al [19], na região III, a deformação progride de forma acelerada com o aumento da taxa de deformação e o processo tende a ser adiabático. Sob tais condições, a geração de calor devido à deformação, principalmente após a estricção localizada, foi mais rápida que a difusão de calor em toda a amostra, resultando em um aumento de temperatura substancialmente maior para os experimentos com taxas de deformação mais altas.…”
Section: Resultsunclassified